2006
DOI: 10.1007/s10531-006-9014-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Characteristics of Reserve Network Selection Using Population Data Versus Habitat Surrogates

Abstract: The use of species data versus environmental surrogates used in lieu of species data in systematic reserve site selection is still highly debated. We analyse in a case study whether and how the results of reserve network selection are affected by the use of species data versus habitat surrogates (habitat models) for qualitative (presence/absence) and quantitative (population size/habitat quality) information. In a model region, the postmining landscape south of Leipzig/Germany, we used iterative algorithms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Unfortunately, knowledge on population viability is currently available only for some single, well-studied species (Henle et al 2004b;Lindenmayer et al 2006;Newbold and Siikamäki 2009;http://www.ufz.de/pva/) and the PVA literature is very heterogeneous posing major challenges for attempts to generalize extinction risks to contexts beyond the original study. Altmoos and Henle (2007) suggested to use abundance within a site as a proxy for extinction risks and to include those sites that harbor the largest population of each species as a constraint for the selection of reserve site network. As population size is a particular good predictor of extinction risk (Henle et al 2004b) and because the required data are not difficult to obtain, this is a promising approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, knowledge on population viability is currently available only for some single, well-studied species (Henle et al 2004b;Lindenmayer et al 2006;Newbold and Siikamäki 2009;http://www.ufz.de/pva/) and the PVA literature is very heterogeneous posing major challenges for attempts to generalize extinction risks to contexts beyond the original study. Altmoos and Henle (2007) suggested to use abundance within a site as a proxy for extinction risks and to include those sites that harbor the largest population of each species as a constraint for the selection of reserve site network. As population size is a particular good predictor of extinction risk (Henle et al 2004b) and because the required data are not difficult to obtain, this is a promising approach.…”
Section: Discussionmentioning
confidence: 99%
“…Wessels et al 1999;Cowling and Heijnis 2001;Faith et al 2001;Trakhtenbrot and Kadmon 2005) does not overcome aspects of temporal variability of species data, instead they might increase the uncertainty whether the network is effective or not (Altmoos and Henle 2007). Firstly, it cannot be taken for granted that surrogates inferred from environmental variables reveal a reliable correlation to species occurrences (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, SDM results can be used. However, it has been found that prioritization results based on SDMs and species presence data may markedly differ (Altmoos and Henle 2007).…”
Section: Spatial Conservation Prioritization (Iii)mentioning
confidence: 99%